EMANCIPATION IN THE AMERICAN ARTISTIC CONSCIOUSNESS OF THE XIX CENTURY - Fisun, Kateryna H. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
This article is devoted to the research of discourse of emancipation in American artistic consciousness on examples of abolitionist novel “Uncle Tom’s Cabin” (1852) by Harriet Beecher Stowe and painting images of XIX century. The topicality of the research is due to insufficient study in Ukrainian philosophy of the ideas of abolitionism and the emancipation of black Americans through the prism of literary images, especially painting images. Among the research tasks are: to analyze topics of slavery and emancipation, ways of representation of racist and abolitionist ideology in the novel’s plot and artistic images; to analyze types of images of “blacks” in literature and painting. Novelty of work is in the reconstruction of emancipation discourse, which confronts with discourse of racism and black Americans’ discrimination in the American literature (on the example of Beecher Stowe’s novel) and in painting images of XIX century. The novel of Harriet Beecher Stowe became a bestseller in Europe and America, the symbol of revolution, it stirred up people’s consciousness in many countries which used different forms of dependency and obligation during XIX – XX century, and later it entered the list of classics of children’s literature. Using the novel as an example, the author shows that the two opposite discourses – colonial (slavery) and anti-colonial (emancipation) are the basis of the controversy of the protagonists, which reflects the social and political controversy over the position and status of black Americans. Ideas of women’s emancipation from gender, social and labor oppression are reflected in the images of black slave women, and in the XX century they became the ideological basis of “black feminism”. Using examples of the novel and painting, the author examines racial and gender stereotypes, the problem of the relationship between “white” and “black”, the problem of preserving the family and women’s resistance to male domination in conditions of slavery, the problem of the formation of national identity in America after the abolition of slavery. The author analyzes the plots in European and American painting, which reflect not only “colonial” images where black Americans are represented as racial and cultural Others, but also “emancipation” images, which symbolically state the resistance to slavery or confirm the subject’s freedom. It is researched in the article that the active development of the emancipation topic in the artistic consciousness shows the change of social status of racial Others in the public consciousness of the XIX century, which was the result of abolitionist and women’s movements for minority rights in America.